2010
DOI: 10.1104/pp.110.162214
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Rice Mitochondrial Carrier Family Reveals Anaerobic Accumulation of a Basic Amino Acid Carrier Involved in Arginine Metabolism during Seed Germination    

Abstract: Given the substantial changes in mitochondrial gene expression, the mitochondrial proteome, and respiratory function during rice (Oryza sativa) germination under anaerobic and aerobic conditions, we have attempted to identify changes in mitochondrial membrane transport capacity during these processes. We have assembled a preliminary rice mitochondrial carrier gene family of 50 members, defined its orthology to carriers of known function, and observed significant changes in microarray expression data for these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 60 publications
1
50
0
Order By: Relevance
“…Here, it was also observed that both clusters 1 and 3 shared overrepresented binding sites for PIF3, ANT, FLC, ABI4, and CDC5, but cluster 3 was also unique in that it contained RAV1, DAG1, and DAG2 binding sites, while cluster 1 contained bHLH binding sites that were not enriched in cluster 3. The binding sites for all these transcription factors have been previously associated with germination, but with reference to the expression of plastid-encoded genes or proteins found in other locations (Peterson, 1977;Ikeda et al, 2009;Groszmann et al, 2010;Lau and Deng, 2010;Taylor et al, 2010;Rizza et al, 2011). Thus, it would appear that the regulation of genes encoding mitochondrial proteins during germination is likely to be under these same mainstream regulatory pathways.…”
Section: Temporal Examination Of Organelle Biogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Here, it was also observed that both clusters 1 and 3 shared overrepresented binding sites for PIF3, ANT, FLC, ABI4, and CDC5, but cluster 3 was also unique in that it contained RAV1, DAG1, and DAG2 binding sites, while cluster 1 contained bHLH binding sites that were not enriched in cluster 3. The binding sites for all these transcription factors have been previously associated with germination, but with reference to the expression of plastid-encoded genes or proteins found in other locations (Peterson, 1977;Ikeda et al, 2009;Groszmann et al, 2010;Lau and Deng, 2010;Taylor et al, 2010;Rizza et al, 2011). Thus, it would appear that the regulation of genes encoding mitochondrial proteins during germination is likely to be under these same mainstream regulatory pathways.…”
Section: Temporal Examination Of Organelle Biogenesismentioning
confidence: 99%
“…The protein content was determined by a modified Bradford assay using bovine serum albumin as a standard (Peterson, 1977). A total of 250 mg was then digested and run on the mass spectrometer as outlined previously (Taylor et al, 2010).…”
Section: Mass Spectrometry Identification Of Proteins Expressed Durinmentioning
confidence: 99%
“…This combination of filters gives SRM approaches their power in complex samples and allows the quantification of many different proteins over 4 orders of magnitude in crude whole-protein extracts from plant tissue samples (Picotti and Aebersold, 2012). SRM MS, also referred to as mass westerns, has previously been used in plants to quantify a number of proteins, including Suc phosphate synthase isoforms in Arabidopsis (Lehmann et al, 2008), Suc synthase isoforms and nitrogen metabolism enzymes in Medicago species , a basic amino acid carrier involved in Arg metabolism in rice (Oryza sativa; Taylor et al, 2010), cytosolic and organelle markers in Arabidopsis (Ito et al, 2011), and the plasma membrane transportome in Arabidopsis (Monneuse et al, 2011). Label-free quantitation in this manner requires reproducibility in sample extraction, digestion, liquid chromatography, and ionization and has been widely reviewed (Lange et al, 2008;Picotti and Aebersold, 2012).…”
mentioning
confidence: 99%
“…Recently, to measure high accurate protein abundances, SRM analysis has been applied to the field of plant science. [19][20][21][22] Lehmann and colleagues have successfully quantified the abundance of four sucrose-phosphate synthase and Tubulin4 (TUB4) transcripts were amplified by PCR in Col-0, pdr9/abcg37-1, pdr9/abcg37-2, and pdr9/abcg37-3 roots grown on basal medium. PDR9/ABCG37 transcript was amplified using primer F1 and R1 for 28 PCR cycles and with primer F1 and R2 for 35 PCR cycles.…”
Section: Determination Of Expression Levels In Mutant Lines By Srm Anmentioning
confidence: 99%